A Case Study on Domestics Spread Of SARS-CoV-2 Pandemic in India - R.Sasikumar, S.Deva Priya, C.Jeganathan (International Journal of Advanced Science and Technology, 2020)
Today talk of the town in the world is about COVID-19. Novel Coronavirus Disease-2019 (COVID-19) is a contagious disease.  Around the globe 2,227, 038 people affected and 150,602 people died by this virus. Still many people are affecting every day. Most of the countries are under lockdown condition even for routine activity. In short period of time, this highly contagious disease made the world into economic crises. There are dozens of vaccines are under research. In this paper we analysed about various diagnosis methods used against SARS-Cov-2 around the world mostly largest population like India. Also presented various approaches following in India for fighting against Coronavirus. Here India’s current scenario about COVID-19 disease has been statistically presented